THE IMPACT OF NETWORK TECHNOLOGIES ON THE TRANSFORMATION OF RUSSIAN HIGHER EDUCATION - Nikolai D. Klikunov (Высшее образование в России)
The purpose of the paper is to identify the conditions under which the development of network technology will help to increase the quality of Russian higher education system. Methods - extrapolation of statistical data, and the construction of an economic model. This article analyzes the causes and consequences of the transition of higher education system of Russia from the regional monopoly to oligopoly in the 1990's of last century and 2000 years of the XXI century. The advantages and disadvantages of getting distance education, and its effect on the quality of higher education in Russia. The paper presents the forecast of the impact of developing network technology on the number of students, the quality of education and universities pricing policy. The author suggests reducing of the number of university teaching staff, increasing the number of students and price abatement for higher education services.